Peran Kota-Kota Kecil Dalam Peningkatan Aktivitas Pertanian Di Kawasan Agropolitan Merapi Merbabu - Mila Wijayanti; Samsul Ma'rif (Jurusan Perencanaan Wilayah dan Kota, 2017)
Agropolitan area is the area with adequate agricultural service for farmers start from pre production to post harvest marketing.The role of small town as a link between big cities as center consumption and villages as center of production are necessary for developing Agropolitan area. Based on these things, analysis the role of small town in Agropolitan area are required. Ngablak, Dukun-Sawangan, Tegalrejo, Grabag, Pakis, and Candimulyo are Small town in Agropolitan area Merapi Merbabu. variables used in this research is commodities area by virtue of conformity land, the city, entanglement small town with local hiterlandny and role of small town as center for trade and service. Method used in this research is quantitative and qualitative descriptive method. Rural urban linkages showed the high interaction in form of linkages economic namely entanglement the shopping flow of farm inputs and capitalization pre agricultural production and marketing of commodities. rural urban linkages also occuring in form of entanglement transportation and relatedness of agricultural technology. Small town in Agropolitan area has a role as a center trade for foods, horticulture vegetables, and horticulture fruits and flowers. Small town in Agropolitan area Merapi Merbabu also has a role as central services for finance, education, and transportation that support the agricultural activity.